136k views
3 votes
F(x) = x + 8
g(x) = 2x2 – 3x – 11
Find: (gof)(2)

2 Answers

4 votes

Answer:

Explanation:

g(f(2))=

f(2)= 2 + 8 = 10

g(10)= 2(10)^2 - 3(10) - 11

2(100) - 30 - 11

200 - 31= 159

User Dorky Engineer
by
4.5k points
5 votes

Answer:

159

Explanation:


(g\circ f)(2) is just another way to express
g(f(2))

This means that you solve what
f(2) is first then input that answer into
g.


f(2)= (2) + 8 = 10\\g(f(2)) = g(10) = 2(10)^2 - 3(10) -11 = 170 - 11 = 159\\

Therefore
(g\circ f)(2) is 159

User Shry
by
5.0k points